Service Sector as an Engine of Growth: Empirical Analysis of Pakistan - Mujahid, Hira; Alam, Shaista (Asian Economic and Financial Review, 2014)
The objective of the present study is to examine the determinants of service sector growth such as external debt, population, gross domestic product per capita, foreign direct investment and government consumption and employed labour force in services. For this purpose the study employed co-integration technique and vector error correction model for investigating long run as well as short run relationship among variables respectively during the annual time period 1976-2010. Results proposed that there is significant effect of population, foreign direct investment, consumption and investment on service sector growth in Pakistan.